Structure and Electronic Properties of an Expanded Terpyridine Complex of Nickel(II) [Ni(ddpd)2](BF4)2 - Dorn, Matthias; Mack, Katharina; Carrella, Luca M.; Rentschler, Eva; Foerster, Christoph; Heinze, Katja (Zeitschrift für Anorganische und Allgemeine Chemie, 2018)
The synthesis, structure in the solid state, electrochemical, magnetic and optical properties of a new nickel(II) complex [Ni(ddpd)2]2+ bearing the tridentate N,N′-dimethyl-N,N′-dipyridin-2-ylpyridine-2,6-diamine (ddpd) ligand are presented. The optical properties are discussed within the framework of ligand field theory.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Ligand field theory; N ligands; Nickel; Spin-flip; Tridentate ligands